Neurovascular Coupling by Functional Near Infra-Red Spectroscopy and Sport-Related Concussion in Retired Rugby Players: The UK Rugby Health Project - Sharma, Anick; Hind, Karen; Hume, Patria; Singh, Jyotpal; Neary, J. Patrick (Frontiers in Human Neuroscience, 2020)
Aim: This study investigated haemodynamic responses to a neurovascular coupling test in retired contact athletes with a history of repeated mild traumatic brain injury (mTBI) and in controls with no history of mTBI. Methods: 21 retired rugby players (47.7 ± 12.9 yr old; age at retirement: 38.5 ± 8.9 yr) with a history of 3 or more diagnosed concussions (8.9 ± 7.9 concussions per player) and 23 controls with no history of mTBI (46.5 ± 12.8 yr old) performed a neurovascular coupling test to detect task orientated haemodynamic changes using functional near-infrared spectroscopy (fNIRS). Results: The neurovascular coupling showed a significant diminished haemodynamic response in comparison to the control group which had a greater relative increase of oxyhaemoglobin (O2Hb). There were reductions in left middle frontal gyrus O2Hb and increases in deoxyhaemoglobin (HHb) in the same region for the mTBI group. These results suggest altered cerebral metabolic demands in participants with a history of multiple head injuries. The mTBI group induced a greater rate of oxygen extraction compared to the control group. Conclusion: This was the first study to examine haemodynamic changes in retired rugby players in response to a neurovascular coupling test and we found reduced cerebral haemodynamic responses in participants with a history of mTBI compared to controls. Further research is needed to ascertain an understanding of the changes in haemodynamics from playing, into retirement.